2002
DOI: 10.1046/j.1462-5822.2002.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

PKSP-dependent reduction of phagolysosome fusion and intracellular kill ofAspergillus fumigatusconidia by human monocyte-derived macrophages

Abstract: SummaryPreviously, we described the isolation of an Aspergillus fumigatus mutant producing non-pigmented conidia, as a result of a defective polyketide synthase gene, pksP ( polyketide synthase involved in pigment biosynthesis). The virulence of the pksP mutant was attenuated in a murine animal infection model and its conidia showed enhanced susceptibility towards damage by monocytes in vitro. Because macrophagemediated killing is critical for host resistance to aspergillosis, the interaction of both grey-gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
103
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 38 publications
7
103
0
1
Order By: Relevance
“…The presence of melanin in A. fumigatus and other fungi is considered to be important for viru-lence because it affects the immune response to fungal infection (38). We observe some dephasing in the aromatic carbon region in the 13 C{ 15 N}REDOR experiments that is consistent with melanin (example structure in Table 1) (39,40), but due to the overlap of 15 N chemical shifts of amides and indoles (near 120 ppm) in the 15 N spectrum, it is not possible to unambiguously identify whether the indole nitrogens are specifically attributed to melanin.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of melanin in A. fumigatus and other fungi is considered to be important for viru-lence because it affects the immune response to fungal infection (38). We observe some dephasing in the aromatic carbon region in the 13 C{ 15 N}REDOR experiments that is consistent with melanin (example structure in Table 1) (39,40), but due to the overlap of 15 N chemical shifts of amides and indoles (near 120 ppm) in the 15 N spectrum, it is not possible to unambiguously identify whether the indole nitrogens are specifically attributed to melanin.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that a functional pksP gene is associated with a reduction in phagolysosome fusion in human monocyte-derived macrophages (MDMs). Consistently, the intracellular killing of pksP mutant conidia by MDMs was significantly greater than the intracellular killing of wild-type conidia (25). By using the enhanced green fluorescent protein, it was shown that the pksP gene was expressed during sporulation.…”
mentioning
confidence: 86%
“…Recently, the group of J. Kwon-Chung and our group identified a gene that encodes a pathogenicity determinant. This gene was designated pksP (or alternatively alb1) for polyketide synthase involved in pigment biosynthesis (23,24,25,28,54). Conidia of a pksP mutant strain are white.…”
mentioning
confidence: 99%
“…neoformans secrete proteins and polysaccharides that lead to the formation of abnormal phagosomes (65)(66)(67). A. fumigatus possesses a surface-bound structure (1,8-dihydroxynaphthalene-like melanin) that has been proposed to inhibit lysosomal fusion in human MDMs (68). Bacterial processes that lead to disruptions of phagosome maturation have been studied in greater detail and might provide hints about the nature of the UV light-indestructible factor of C. glabrata.…”
Section: Glabrata Blocks Phagolysosome Formation and Phagosome Acimentioning
confidence: 99%